Efficacy of the Therapeutic Game “Trisquel” in the Treatment of Patients With Substance-Related Disorders Randomized Clinical Study - Piñón-Blanco, Adolfo; Vergara-Moragues, Esperanza; Gutiérrez-Martínez, Olga; Fernández-Palleiro, Patricia; Rodrigues, Sonia; Rodrigues-Amorím, Daniela; Lage-López, María Teresa; González-López, Ana; Velasquez, Teresa; Amorim, Mónica; Lloves-Moratinos, Manuel; Viéitez-Fernández, Isabel; et al. (Frontiers in Psychiatry, 2022)
Substance-related disorders (SRD) have been consistently associated with alterations both in cognitive and executive functions, which affect to patients’ quality of life. The main objective of this work was to test the beneficial cognitive effects on patients with SRD after the implementation of “Trisquel,” an intervention program in board game format. To check the effectiveness of Trisquel program, a group of people diagnosed with SRD was randomly assigned either to the experimental group or to the control group. The experimental group performed Trisquel structured sessions twice a week during 3 months, while the control group performed routinely conventional therapeutic activities with the same frequency and duration. Neuropsychological tests were done to both groups before and after the intervention. After the 3 months of intervention the experimental group showed the following statistically significant improvements for WAIS-III subtests: number key, symbol search, arithmetic, direct digits, inverse digits, total digits, letters-numbers in the processing speed index and in the working memory index. Regarding STROOP tests, statistically significant progress was observed in the phonetic fluency letter P, phonetic fluency letter M, phonetic fluency letter R subtests, word-reading and word-color subtests. The control group only obtained improvements for WAIS-III subtests of arithmetic, letters-numbers and in the working memory index. The results of this study confirm that “Trisquel” is an effective intervention program for people diagnosed with SRD, getting improvements in processing speed (psychomotor and reading), attentional subprocesses (focused and sustained) and executive functions (updating and inhibition).